The Significance of Malate Dehydrogenase Isoenzymes in Human Blood Platelets - Schneider, W; Gross, R (Thrombosis and Haemostasis, 1975)
Two MDH isoenzymes were detected in the homogenate of normal human blood platelets. According to their properties the cationic isoenzyme is compartmentalized in the mitochondria, the anionic one belongs to the cytoplasma. In spite of the few mitochondria in human blood platelets the proportion of the cationic enzyme is relatively high.Both of these enzymes could belong to a transfer system for malate transport across the mitochondrial membrane. As human blood platelets do not contain creatine phosphate a system like that could be of significance for platelet function.